Settlement of Disputes over Workers' Wage Rights Based on Law No. 13 of 2003 concerning Manpower and Law No. 2 of 2004 concerning the Settlement of Industrial Relations Disputes - Meliana Fadia Kartika; Jaenudin Umar (Jurnal Legisci, 2026)
Background. Wages are normative rights and basic rights of workers that arise from the employment relationship between workers and employers. Wages not only serve as a reward for the energy and time that workers have given, but also as a means to guarantee a decent livelihood for workers and their families. Therefore, the state is obliged to provide legal protection for the fulfillment of workers' wage rights through the regulation and mechanism of resolving industrial relations disputes. Although Law No. 13 of 2003 concerning Manpower and Law No. 2 of 2004 concerning the Settlement of Industrial Relations Disputes have regulated wage rights and their settlement mechanisms, in practice there are still frequent wage violations that give rise to rights disputes. Purpose. This study aims to analyze the legal arrangements regarding workers' wage rights under Law Number 13 of 2003 and to examine the mechanism for resolving disputes over workers' wage rights under Law Number 2 of 2004. Method. The research method used is normative juridical research with a statutory approach and a conceptual approach. The legal materials used consist of primary, secondary, and tertiary sources collected through literature reviews and analyzed qualitatively. Results. The results of the study show that the legal arrangements regarding workers' wage rights have normatively provided clear and comprehensive protections, including the obligation of employers to pay wages on time, the prohibition on wage payments below the minimum wage, and the regulation of sanctions for wage violations. However, in industrial relations practice, there remains a gap between legal norms and their implementation due to weak labor supervision, low worker legal awareness, and a lack of firmness in law enforcement. Conclusion. The mechanism for resolving wage disputes through bipartite negotiations, mediation, conciliation, and Industrial Relations Courts has been regulated in stages, but has not been fully effective in providing optimal legal protection for workers. Implementation. It is necessary to strengthen the state's role through increased supervision, consistent law enforcement, and legal education for workers to ensure the fulfillment of wage rights in a fair and equitable manner.